(untitled) (Revista de História Regional, 2025)
Throughout this presentation, we briefly discuss the studies that comprise the dossier "Rural World, Diverse Lives: Experiences, Work, and Culture." This dossier brings together studies that address the Brazilian rural world from multiple dimensions: historical, social, political, and cultural. The articles presented here are situated between the colonial period and the 21st century and analyze themes such as land conflicts, migration, labor, political repression, monocultures, territorialities, and cosmologies. From a historical perspective, in dialogue with sociology, anthropology, and geography, the texts highlight the complexity of rural experiences and the protagonism of subjects often rendered invisible by traditional historiography. The articles in the dossier draw on diverse sources such as official documents, interviews, oral histories, ethnographic accounts, and others, proposing new ways of interpreting the rural world not only as a productive space, but also as a territory of disputes, resistance, knowledge, and meaning.